Investigation of the efficacy of generic and brand-name tiotropium bromide in the management of chronic obstructive pulmonary disease: A randomized comparative trial - Yunes Panahi; Mostafa Ghanei; Mohammad Behzadi; Maryam Salehi; Sara Saffar Soflaei; Amirhossein Sahebkar (Elsevier, 2016)
Introduction: The beneficial effects of tiotropium bromide, a long acting anticholinergic bronchodilator, in the management of chronic obstructive pulmonary disease have been shown in previous studies. The present study aimed to compare the efficacy and safety of generic (Tiova®) and brand-name (Spiriva®) tiotropium preparations in patients with COPD. Methods and materials: In this randomized double-blind parallel-group trial, 79 patients with documented COPD were assigned to Tiova® or Spiriva® for a period of 4 weeks. Assessment of pulmonary function (using spirometry), quality-of-life (using St. George respiratory Questionnaire [SGRQ]) and severity of respiratory symptoms (using breathlessness, cough and sputum scale [BCSS]) was performed at baseline and at the end of treatment period. Results: There were significant increases in FEV1 and reductions in FVC by the end of study in both Tiova® and Spiriva® groups. FEV1/FVC ratio did not change significantly neither in the Tiova® nor in Spiriva® group. Overall SGRQ score as well as subscale scores of symptoms, activity and impacts were improved by both drugs. In the BCSS scale, the frequency and severity of three main symptoms (dyspnea, cough and sputum) was decreased by both drugs. Baseline as well as post-treatment values of spirometric parameters, SGRQ and BCSS scores was comparable between the groups, apart from a lower post-treatment frequency of cough and sputum in the Spiriva® versus Tiova® group. There was no report of adverse events in either of the study groups. Conclusion: The findings of this comparative trial showed equivalent efficacy and safety of Spiriva® and Tiova® in lessening the symptoms as well as improving the quality of life in patients with COPD. This finding has an important translational value given the significantly lower costs of generic versus brand-name products.